Idiopathic Pulmonary Fibrosis: Review of Current Knowledge - Muri, J; Durcová, B; Slivka, R; Vrbenská, A; Makovická, M; Makovický, P; Škarda, J; Delongová, P; Kamarád, V; Vecanová, J (Physiological research, 2024)
Idiopathic pulmonary fibrosis (IPF) is a severe and currently incurable disease that is associated with irreversible fibrotic remodeling of the lung parenchyma. Pathological remodeling of the lung leads to damage of the alveolo-capillary barrier. There is a reduction in the diffusing capacity of the lungs for respiratory gases. Later, changes in the mechanical properties of lung tissue occur - their compliance decreases and respiratory work increases. Impaired respiratory gases exchange with restrictive ventilatory failure lead to tissue hypoxia and muscle weakness. Progressive respiratory insufficiency develops. The triggers of fibrotic remodeling of the lung are currently unknown, as are the pathomechanisms that keep this process active. IPF can only be slowed pharmacologically, not reversed. It is therefore very important to start its treatment as soon as possible. Early detection of IPF patients requires a multidisciplinary approach. Diagnosis, treatment initiation, and monitoring in specialized centers offer the best chance of slowing disease progression, enhancing quality of life, and extending patient survival. In addition to antifibrotic therapy, good lifestyle management, maintenance of physical fitness and treatment of associated chronic diseases such as diabetes and cardiac comorbidities are important. Lung transplantation is an option for some patients with IPF. This is a challenging treatment modality, requiring close collaboration with transplant centers and expert selection of suitable candidates, influenced, among other things, by the availability of suitable donor lungs. Our article aims to provide current information about IPF, focusing on its functional consequences and clinical manifestation. We discuss the molecular and cellular mechanisms potentially involved in IPF development, as well as the morphological changes observed in lung biopsies and high-resolution computed tomography (HRCT) images. Finally, we summarize the existing treatment options. Key words: Idiopathic pulmonary fibrosis, Lung biopsy, HRCT, Antifibrotic therapy, Lung transplantation.
Keywords: Lung Transplantation; Lung; Animals; Humans; Idiopathic Pulmonary Fibrosis; lidé; zvířata; idiopatická plicní fibróza; plíce; transplantace plic